2019
DOI: 10.1016/j.neuroimage.2019.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal neuroimaging of dual-task walking: Structural MRI and fNIRS analysis reveals prefrontal grey matter volume moderation of brain activation in older adults

Abstract: It has been well established over the last two decades that walking is not merely an automatic, motoric activity; it also utilizes executive function circuits, which play an increasingly important role in walking for older people and those with mobility and cognitive deficits. Dual-task walking, such as walking while performing a cognitive task, is a necessary skill for everyday functioning, and has been shown to activate prefrontal lobe areas in healthy older people. Another wellestablished point in healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 105 publications
(173 reference statements)
5
50
1
Order By: Relevance
“…This may be mainly due to the simplicity of the application over hairless areas and can be overcome with better probe designs. Furthermore, differences in cerebral activation patterns detected by fNIRS could be actually related to structural alterations, as recently reported in an MRI-fNIRS study (Wagshul et al, 2019) where higher activation in healthy older adults during DT was related to reduced cortical volumes, especially in bilateral superior and rostral-middle frontal cortex. More evidence is needed supporting this concept.…”
Section: Methodological Aspects and Limitationssupporting
confidence: 57%
“…This may be mainly due to the simplicity of the application over hairless areas and can be overcome with better probe designs. Furthermore, differences in cerebral activation patterns detected by fNIRS could be actually related to structural alterations, as recently reported in an MRI-fNIRS study (Wagshul et al, 2019) where higher activation in healthy older adults during DT was related to reduced cortical volumes, especially in bilateral superior and rostral-middle frontal cortex. More evidence is needed supporting this concept.…”
Section: Methodological Aspects and Limitationssupporting
confidence: 57%
“…A recent review emphasized the importance of examining brain structure and function relations in aging and MCI using MRI methods [57]. Previous work demonstrated that white matter integrity [58] and grey matter volume [59] moderated fNIRS-derived HbO 2 levels assessed during active walking in participants aged 65 or older. It would, therefore, be of importance to examine whether the structural integrity of the brain also influences the changes in fNIRS-derived HbO 2 due to walking conditions and training in participants with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an association of DT performance (i.e., processing speed and executive function) and the gray matter volume of various areas of motor control including PFC ( Allali et al, 2019 ; Blumen et al, 2019 ; Tripathi et al, 2019 ). Albeit structure-function evaluations of these regions are scarce, first evidence indicates the potential moderator role, which brain prefrontal activation can have on volume loss in elderly ( Wagshul et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%